(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
At present, new production facilities equipped with modern, advanced technologies are being launched in our country. Ensuring industrial, technical safety, labor protection and production stability are important tasks at these facilities. When performing these tasks, the optimization of the scientific direction of the use of personal protective equipment for protection against accidents and injuries that may occur in enterprises, in particular at hazardous and harmful production facilities, is a difficult task.